Analisis Daya Saing Ekspor Minyak Kelapa Mentah Indonesia Periode 2015–2024 di Pasar Internasional dengan Pendekatan RCA, RSCA, Growth RCA, dan EPD - Sri Oktapiani; Rizqi Muttaqin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Crude coconut oil (crude coconut oil) is one of the vegetable oil commodities that plays an important role in international trade. Indonesia, as one of the largest coconut producers in the world, has great potential in exporting crude coconut oil; however, its performance remains volatile and faces competition from major rival countries, particularly the Philippines. This study aims to analyze the export competitiveness of Indonesian crude coconut oil in the international market during the period 2015–2024. The study employs a descriptive quantitative approach using secondary data sourced from ITC Trade Map and UN Comtrade. The analytical methods applied include Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), Growth RCA, and Export Product Dynamics (EPD). The results indicate that Indonesia's crude coconut oil exports have a comparative advantage (RCA > 1), but their competitiveness is not yet stable and is relatively lower than that of the Philippines. The EPD analysis places Indonesian crude coconut oil in the Retreat category, indicating that both Indonesia's export market share growth and global demand growth for crude coconut oil tend to weaken simultaneously. These findings suggest that Indonesia's comparative advantage in crude coconut oil has not yet been converted into dynamic export competitiveness, as reflected in the Retreat position in the EPD analysis and the fluctuating competitiveness growth during the study period.